PROTEIN PROFILING FOR PHYLOGENETIC RELATIONSHIP IN Tilapia guineensis FROM SOUTH-WEST NIGERIAN WATER BODIES - Ukenye, E. A; Megbowon, I.; Akinwale, M. M. A.; Jibrin, H.; Sokenu, B. A.; Olagunju, G. E. (Nigerian Journal of Fisheries, 2018)
Tilapia guineensis is one of the important Cichlid species with good aquaculture potential, economic and nutritional value commonly found in Nigerian coastal waters. Protein electrophoresis was used to determine intra and inter-specific variation among populations. The protein banding pattern of four Tilapia guineensis populations from two different states (Ondo and Lagos; two locations per state) of South-west Nigeria were used to study the phylogenetic relationship among them. The scoring of the gel images obtained after electrophoresis was done and data generated were subjected to cluster analysis. The banding pattern from sarcoplasmic protein indicated a unique profile for two populations (Pepe and Epe) and the electrophoregrams showed similarities among the populations indicating some levels of genetic affinity while Ugbonla and Badagry showed variation in their banding pattern. The molecular weight of the protein bands varied from 20 kDa - 250 kDa. Analysis of molecular variance (AMOVA) demonstrated that genetic variation was mostly among populations. Unweighted Pair Group Method with Arithmetic Mean (UPGMA) dendrogram revealed patterns of genetic variability among these populations. These results provide useful baseline genetic information for breeding and conservation of T. guineensis populations.